Innovations in Lifestyle Intervention Programs for People with Diabetes Mellitus: A Multidisciplinary Approach - Maria Karolina Selano; Kristiana Prasetia Handayani; Ariani Damayanti; Oke Dwi Astuti; Nike Dewi Mardhiyaningsih (GLOBAL HEALTH SCIENCE GROUP, 2025)
Diabetes mellitus is one of the significant global health problems, including in Indonesia, which is estimated to have a prevalence of up to 12% of the adult population by 2025. The disease causes serious complications, lowers the patient's quality of life, and increases the economic burden. An innovative, integrated multidisciplinary approach to lifestyle interventions is necessary for effective diabetes management. This study aims to develop and evaluate the effectiveness of multidisciplinary lifestyle intervention programs that include nutrition, physical activity, psychological support, and health education in the treatment of Diabetes Mellitus in patients at the Kgok Health Center, Semarang. This study uses a quasi-experimental design with a design of two pre-test and post-test groups. The sample in this study was selected using a purposive sampling technique consisting of 60 people with diabetes mellitus who were divided into two groups: the intervention group (n=30), who underwent an integrated lifestyle program, and the control group (n=30), who received standard care. Evaluation was carried out before and after the intervention for 1 month. The effects of the program were measured through a self-efficacy questionnaire, while health parameters included fasting blood sugar levels, blood pressure, and body mass index (BMI). Data normality tests were used using Shapiro-Wilk, and pre-post differences between groups were analyzed with Mann-Whitney tests due to abnormal data distribution (p< 0.05). The results showed that there was a significant influence on self-efficacy scores and decreased blood sugar and blood pressure levels in the intervention group compared to controls with a p< value of 0.05. Multidisciplinary lifestyle intervention programs are effective in improving the management of Diabetes Mellitus as well as the quality of life of patients. The output of this research became the basis for the development of educational modules for health workers and made an important contribution to the implementation of sustainable interventions in Indonesia.